2019
DOI: 10.3389/fneur.2019.00621
|View full text |Cite
|
Sign up to set email alerts
|

Severe Constipation in Parkinson's Disease and in Parkinsonisms: Prevalence and Affecting Factors

Abstract: Background: constipation is one of the most common and disabling non-motor symptoms of Parkinson Disease (PD) and Parkinsonisms (PS). Few studies evaluate the difference of prevalence between PD and PS and the cause leading to a severe constipation in this diseases. Objective: Aim of our study is to evaluate the prevalence of constipation in a population of patients with PD and PS and to evaluate which factors influence the development of severe constipation. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…Although we did not complete a statistical analysis of Medopa dosage alone, this study showed no difference between LEDs in Cons-PD and nCons-PD groups, being consistent with Frazzitta et al (28) but contrary to Zhang and Liu's (29) findings. The possible lack of correlation between LED and constipation is worthy of consideration as some authors have previously attributed constipation to dopaminergic treatment (30).…”
Section: Discussionsupporting
confidence: 87%
“…Although we did not complete a statistical analysis of Medopa dosage alone, this study showed no difference between LEDs in Cons-PD and nCons-PD groups, being consistent with Frazzitta et al (28) but contrary to Zhang and Liu's (29) findings. The possible lack of correlation between LED and constipation is worthy of consideration as some authors have previously attributed constipation to dopaminergic treatment (30).…”
Section: Discussionsupporting
confidence: 87%
“…The hallmark clinical symptom of PD is motor impairment (i.e., rigidity, movement slowness, resting tremor, among others [ 4 , 5 , 6 ]), which is first noticeable when there is already 40–60% neuronal loss in the substantia nigra (SN) [ 7 , 8 ]. However, clinical features include non-motor symptoms such as depression [ 9 ], REM-sleep behavior disorder [ 10 , 11 ], autonomic dysfunction [ 12 ], olfactory disruption [ 13 ], and constipation [ 14 , 15 ], among others. In the past 15 years, non-motor PD symptoms have raised a lot of attention because they can occur years before the onset of motor symptoms [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to emergency ileus in PD, 4,15 no such condition occurs in SSD except for patients under longstanding antidepressive medication. Thus, constipation is regarded the major GI form of SSD 24 . In patients with depression, functional test (urodynamics) often reveals increased bladder sensation, followed by underactive detrusor 18–20 .…”
Section: Discussionmentioning
confidence: 99%